Returning from Practice to Theory to Practice too - Boelt, Anders Melbye; Møller, Anders Kalsgaard; Lyngbye, Marie Charlotte (Proceedings for the European Conference on Reflective Practice-based Learning 2025, 2025)
Contemporary aspirations of higher education emphasise various conceptions of employability and ready-to-work students. This is often included in education as authentic problems parting from prospective vocational practices or different types of apprenticeship, thus reciprocally enriching theorical insights with practical actions for the becoming novice, student. Practice becomes a space entangled in specific pedagogical approaches and considerations. However, the opposite also happens, practice returning to education, where practitioners with years of vocational experience return. This paper presents a case study of an educational Master’s program consisting of both students continuing the education from a bachelor program, and practitioners returning to education. Based on Dewey’s experiential continuum, we investigate how we by non-intrusive means can aid students’ (N = 28) in reflecting on their past, present and anticipated future in relation to the educational program. The data consist of short, personal snapshots containing short personal characteristics, motivations, and career prospects written by the students on post-it notes (N = 311). The post-its were collected on the first day of study through a workshop. The snapshots show a wide variation in students’ rationales and ambitions, such as technical and generic competence development, modes of studying, aspirations to change career and profession, but also personal aspects such as family life. A common denominator is a shared story about ambitions to change current careers or open new avenues for employment and professional practice.